Measurement of the charm-mixing parameter γCP - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Physical review letters, 2019)
A measurement of the charm-mixing parameter yCP using D0→K+K−, D0→π+π−, and D0→K−π+ decays is reported. The D0 mesons are required to originate from semimuonic decays of B− and ¯¯¯B0 mesons. These decays are partially reconstructed in a data set of proton-proton collisions at center-of-mass energies of 7 and 8 TeV collected with the LHCb experiment and corresponding to an integrated luminosity of 3 fb−1. The yCP parameter is measured to be (0.57±0.13(stat)±0.09(syst))%, in agreement with, and as precise as, the current world-average value.